(untitled) (World Bulletin of Public Health, 2025)
Aging of the body is a complex process characterized by a weakening of oxidative processes in the body and associated energy potentials and a decrease in the function of vital organs. Rational nutrition in old age (geroidetics) is an important factor in the preservation and restoration of vital body processes. The article provides the basic principles of nutrition for elderly and elderly people